2010
DOI: 10.1007/s00436-010-2110-9
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the knowledge of Culicoides (Diptera: Ceratopogonidae) host preferences in France

Abstract: Knowledge on host-feeding pattern of blood-sucking insects helps to understand the epidemiology of a vector-born disease. We determined blood meal origin from blood-fed Culicoides thanks to molecular techniques. A set of primers was used to selectively amplify segment of vertebrates' prepronociceptin gene from abdomen of engorged Culicoides (Diptera: Ceratopogonidae). Vertebrate DNA was successfully amplified in 91% of blood-fed Culicoides assayed. Direct sequencing and comparison of resultant sequences with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 31 publications
7
73
0
2
Order By: Relevance
“…C. obsoletus also seemed to be attracted to heifer, goat and ewe, as well as birds (Viennet et al, 2013), although this species is considered to be strictly mammalophilic (Lassen et al, 2012). While some Culicoides species are opportunistic, most Palaearctic species appear to prefer cattle (Bartsch et al, 2009;Lassen et al, 2011;Ninio et al, 2011). Ninio et al (2011) identified the blood of horse, rabbit, pig, sheep and human in the abdomens of blood-fed C. obsoletus females, whereas Pettersson et al (2013) observed the blood of sheep, cattle and horse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C. obsoletus also seemed to be attracted to heifer, goat and ewe, as well as birds (Viennet et al, 2013), although this species is considered to be strictly mammalophilic (Lassen et al, 2012). While some Culicoides species are opportunistic, most Palaearctic species appear to prefer cattle (Bartsch et al, 2009;Lassen et al, 2011;Ninio et al, 2011). Ninio et al (2011) identified the blood of horse, rabbit, pig, sheep and human in the abdomens of blood-fed C. obsoletus females, whereas Pettersson et al (2013) observed the blood of sheep, cattle and horse.…”
Section: Discussionmentioning
confidence: 99%
“…While some Culicoides species are opportunistic, most Palaearctic species appear to prefer cattle (Bartsch et al, 2009;Lassen et al, 2011;Ninio et al, 2011). Ninio et al (2011) identified the blood of horse, rabbit, pig, sheep and human in the abdomens of blood-fed C. obsoletus females, whereas Pettersson et al (2013) observed the blood of sheep, cattle and horse. This species, thus, seems to feed on a wide range of mammals (Lassen et al, 2012) but to prefer cattle, even when other hosts are present in adjacent areas (Bartsch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seroprevalences in cattle and small ruminants reached up to 100%. Similarly to BTV, SBV overwintered in many geographic areas (6,21,25), including Poland, and reappeared again in 2012 and 2013 spreading across the whole continent (5). While BTV ability to survive the winter has not been explained, the transovarial transmission of SBV in the midges has been suggested (14).…”
Section: Introductionmentioning
confidence: 99%
“…Cela pourrait s'expliquer par la recherche d'un endroit où leurs hôtes potentiels sont nombreux, proches les uns des autres et peu mobiles ; le régime alimentaire hématophage des femelles adultes pourrait ainsi être assuré. Même si les bovins semblent être les hôtes privilégiés par de nombreuses espèces paléarctiques du genre Culicoides Ninio et al 2011a), la plupart de ces moucherons piqueurs peuvent en effet avoir un comportement alimentaire opportuniste (Garros et al 2011). Ils sont par conséquent susceptibles de réaliser leur repas sanguin sur une large gamme d'hôtes, dont les ovins.…”
Section: Traitement Des éChantillons Et Analyseunclassified